Data, the future of science and clinical Practice - González-Méijome, José Manuel (2020)
[Excerpt] The statement posed in the title of this editorial that seems so obvious, is not that obvious for several reasons. First, data presents in very different shapes and sizes, and in many cases it is the size that matters when it comes to claim conclusions, the advance of scientific and clinical knowledge and reach the society by improving people quality of life. However, most of clinical evidences use to be derived from rather small or short-term trials, eventually summed up in systematic reviews and more recently in meta-analysis to arrive to more solid and robust conclusions. Second, the explosion of research efforts and publications in those fields has frequently increased the controversy of the results reported, what in some instances confound the scientific community. Particularly vulnerable in this regard are clinicians who have to decide which diagnostic tools and treatment options to trust and apply to their patients. If there might be a statistical/probabilistic justification to this increased discrepancy of results, there is also a growing evidence that data generated sometimes can be of doubtful confidence either regarding the way it were obtained, analyzed or whether they exist at all!!. This has led to a crisis in reproducibility and trust in science that has been the object of many recent editorials, internet publications and other academic publications. [....]